Antidiarrhoeal Activity of Methanolic Extract of Acacia farnesiana Bark - Misar, Ashwini; Mujumdar, A.M. (Asian Journal of Chemistry, 2010)
Based on ethno-botanical use the bark of Acacia farnesiana Willd. (family-Mimosaceae) was studied for the antidiarrhoeal activity. Bark of Acacia farnesiana was successively extracted with petroleum ether, methanol and distilled water. The extracts were dried under reduced temperature and pressure. The methanolic extract of Acacia farnesiana bark (AFM) showed significant antidiarrhoeal activity in exploratory studies. The methanolic extract of Acacia farnesiana bark at 100, 200 and 400 mg/kg, p.o. produced a significant and dose dependent inhibition of in castor oil induced diarrhoea. Therefore methanolic extract of Acacia farnesiana bark was studies in detail for magnesium sulphate induced diarrhoea, intraluminal fluid accumulation and normal as well as barium chloride induced charcoal transit. Antimicrobial activity of methanolic extract of Acacia farnesiana bark against diarrhoea causing micro-organisms has also been studied in vitro. The methanolic extract of Acacia farnesiana bark showed significant inhibition of castor oil and magnesium sulphate induced diarrhoea. It also inhibits fluid accumulation against castor oil challenge in enteropooling assay. The methanolic extract of Acacia farnesiana bark reduced normal as well as barium chloride induced peristalsis of small intestine in mice. The methanolic extract of Acacia farnesiana bark also showed antimicrobial activity against common pathogens responsible for diarrhoea in vitro.